Preparation of an ultra-thin nickel-aluminum hydrotalcite sheet material and its application in removing Cr(VI) from wastewater and soil

By introducing formamide and ultrasonic waves in the synthesis of nickel-aluminum hydrotalcite, an efficient ultra-thin nickel-aluminum hydrotalcite sheet material was prepared, which solved the low efficiency and high cost of removing hexavalent chromium in wastewater and soil in the prior art. Problem, efficient Cr(VI) adsorption and environmental repair are achieved.

CN118698522BActive Publication Date: 2025-02-14SHANDONG UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410696334.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-31
Publication Date
2025-02-14
Estimated Expiration
2044-05-31

AI Technical Summary

Technical Problem

The prior art has the risk of low efficiency, high cost and secondary pollution in removing hexavalent chromium (Cr(VI)) in wastewater and soil, especially chemical precipitation methods and partial adsorption methods.

Method used

Using ultra-thin nickel-aluminum hydrotalcite sheet material (NiAl-LDH), the introduction of formamide and ultrasonic waves in the synthesis of nickel-aluminum hydrotalcite can be prepared to produce efficient colloidal materials, and by adjusting pH and using alkaline solutions. Promote the formation of NiAl-LDH.

Benefits of technology

It significantly enhances the adsorption capacity of the material to hexavalent chromium, reduces the thickness of the sheet, improves the removal efficiency, is suitable for water treatment and soil restoration, and provides an effective and reliable environmental restoration method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118698522B_ABST
    Figure CN118698522B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of an ultra-thin nickel-aluminum hydrotalcite sheet material, and belongs to the technical field of heavy metal pollutant removal. In the present invention, by introducing formamide and microwaves in the synthesis process of nickel-aluminum hydrotalcite, the accumulation of sheets is significantly suppressed, the thickness of the sheets is reduced, and the adsorption capacity of hexavalent chromium is enhanced. Nickel, as the main active component, has unique chemical properties, such as excellent redox ability and stable chemical structure, so that NiAl-LDH shows excellent effects in removing heavy metal ions. The NiAl-LDH material prepared by this method can be widely used in the fields of water treatment and soil remediation, especially in the removal of toxic hexavalent chromium. This material is not only suitable for industrial wastewater treatment, but also suitable for the remediation of contaminated soil, providing an effective and reliable solution for environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heavy metal pollutant removal, and specifically relates to the preparation of an ultra-thin nickel-aluminum hydrotalcite sheet material and its application in removing Cr(VI) from wastewater and soil. Background Art

[0002] Heavy metal pollution, especially hexavalent chromium (Cr(VI)), has become a pressing issue in today's environment. Cr(VI) is mainly derived from industrial activities such as leather tanning, electroplating, metal plating and chemical manufacturing. Improper treatment and leakage of industrial waste generated during these activities have caused significant pollution to the water and soil environment. Cr(VI) exists in the form of hydrophilic oxide anions. Due to its high mobility and toxicity, it has a stronger mobility in the environment than cationic heavy metals, making it more difficult to manage. This mobility allows them to accumulate in plants and ultimately affect humans through the food chain, posing a potential threat to the environment and human health. Ingestion of food or water containing Cr(VI) may cause serious health problems including liver failure, kidney damage, gene mutations and various cancers. Therefore, the remediation of Cr(VI) in soil and water is particularly important. Commonly used hexavalent chromium (Cr(VI)) treatment methods include the following: redox method, chemical precipitation method and adsorption method.

[0003] However, these methods have some defects to a greater or lesser extent. For example, chemical precipitation requires a large amount of reagents, has high processing costs, and may cause secondary pollution. Among them, adsorption is recognized as one of the most widely used methods due to its simple operation, high efficiency and low cost. Therefore, in order to find more effective and sustainable solutions to mitigate the impact of heavy metal pollution, it is crucial to continue research and development in this field. At present, a variety of adsorbents such as activated carbon, alumina, natural clay minerals, etc. have been synthesized and used in academic research and industrial applications. Summary of the invention

[0004] The purpose of the present invention is to solve the above-mentioned problems and provide a method for preparing an ultra-thin nickel-aluminum hydrotalcite sheet material and its application in removing Cr(VI) from wastewater and soil.

[0005] The technical solution adopted by the present invention is as follows: a method for preparing an ultra-thin nickel-aluminum hydrotalcite sheet material, characterized in that the preparation method comprises the following steps:

[0006] S1: dissolving appropriate amounts of nickel sulfate and aluminum sulfate in deionized water to prepare a metal salt solution;

[0007] S2: The solution is placed in a conical flask to ensure sufficient reaction;

[0008] S3: introducing 2% to 30% by volume of formamide, and promoting the dissolution and reaction of the compound under the assistance of ultrasound;

[0009] S4: Subsequently, while continuously stirring, slowly adding an appropriate amount of alkaline solution to adjust the pH value and promote the formation of NiAl-LDH;

[0010] S5: As the reaction proceeds, a colloidal material is formed, and then the colloidal material is concentrated by centrifugation;

[0011] S6: Then, ethanol is used for multiple washing and centrifugation to remove impurities and unreacted residues, thereby obtaining a high-purity gel-like ultrathin nickel-aluminum hydrotalcite sample FU-NiAl-LDH;

[0012] In the step S1, the molar ratio of nickel to aluminum is 2-3:0.5-1.

[0013] In a preferred embodiment, in step S3, the alkaline solution is a sodium hydroxide solution.

[0014] In a preferred embodiment, in step S4, the pH value of the solution is controlled to be 9-11 during the process of adjusting the pH value and promoting the formation of NiAl-LDH.

[0015] In a preferred embodiment, in step S3, the ultrasonic power is 1 W / cm 2 .

[0016] In a preferred embodiment, an ultra-thin nickel-aluminum hydrotalcite sheet material is used to remove Cr(VI) from wastewater and soil.

[0017] In a preferred embodiment, the application comprises the following steps:

[0018] S1: First, a Cr(VI) aqueous solution of a certain concentration is prepared by dissolving an appropriate amount of K2Cr2O7 in deionized water;

[0019] S2: Then, LDHs were added to the Cr(VI) aqueous solution to conduct adsorption experiments. During the entire removal process, nitrogen was continuously introduced into the solution to maintain an inert atmosphere.

[0020] S3: Performed in a thermostatic oscillator, by setting a specific oscillation rate and temperature. Samples are taken at multiple predetermined time points and filtered through a microporous filter to analyze the remaining Cr(VI) content in the filtrate.

[0021] In a preferred embodiment, the concentration of the Cr(VI) solution is 10-100 mg / L.

[0022] In a preferred embodiment, the concentration of LDHs in the Cr(VI)-containing solution and soil is 5-15 g / L.

[0023] In a preferred embodiment, the constant temperature oscillator has a speed of 100-300 rpm and a temperature of 25-40°C.

[0024] In a preferred embodiment, the sampling time for removing Cr(VI) from the solution is 0 to 60 min;

[0025] The sampling time for removing Cr(VI) from the soil is 0 to 90 minutes.

[0026] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0027] In the present invention, by introducing formamide and microwaves during the synthesis of nickel-aluminum hydrotalcite, the accumulation of lamellae is significantly suppressed, the thickness of the lamellae is reduced, and its adsorption capacity for hexavalent chromium is enhanced. Nickel, as the main active component, has unique chemical properties, such as excellent redox ability and stable chemical structure, so that NiAl-LDH shows excellent effects in removing heavy metal ions. The NiAl-LDH material prepared by this method can be widely used in the fields of water treatment and soil remediation, especially in the removal of toxic hexavalent chromium. This material is not only suitable for industrial wastewater treatment, but also suitable for the remediation of contaminated soil, providing an effective and reliable solution for environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a scanning electron microscope (SEM) image of the hydrotalcite obtained in Example 1 of the present invention.

[0029] Figure 2 This is a transmission electron microscope TEM image of the hydrotalcite obtained in Example 1 of the present invention.

[0030] Figure 3 The concentration of Cr(VI) changes with time in the test example of the present invention.

[0031] Figure 4 The concentration change of Cr(VI) in the soil after adsorption in the test example of the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] Reference Figure 1-4 ,

[0034] Layered double hydroxides (LDHs), as a typical type of anionic clay minerals, show great application potential in fields such as water treatment, especially their anion exchange capacity. The general chemical formula of LDHs is [M2+1-xM3+x(OH)2][An-]x / n·mH2O, where M2+ and M3+ represent divalent and trivalent metal ions, such as Mg2+, Ca2+, Mn2+ (divalent) and Al3+, Fe3+, Co3+ (trivalent). An- is an interlayer anion, such as CO32- or Cl-. In this structure, the x value represents the molar ratio of M3+ / (M2++M3+), which is usually between 0.20 and 0.33 to maintain high purity. LDH is composed of serpentine-like octahedral layers containing M3+, in which part of M2+ is replaced by M3+, thereby generating a positively charged layer. These positive charges are electrically neutralized by interlayer anions, while the interlayer space is occupied by water molecules in the hydration shells of these intercalated anions. The special layered structure of LDHs gives them a variety of remarkable properties, including alkalinity, memory effect, infrared absorption, catalytic properties and anion exchange capacity, as well as controllability of composition and structure. In addition, the preparation of LDHs is simple and low-cost, which makes them occupy an important position in the application of adsorbents.

[0035] A variety of LDHs have been reported to be used to remove heavy metal pollutants in the environment, including MgAl-LDH, NiAl-LDH, ZnAl-LDH, CaAl-LDH, MgFe-LDH and NiFe-LDH. Although LDH has a layered structure, due to the strong interlayer force, common LDHs are all block materials with multiple layers stacked together, with a small available apparent specific surface area, and cannot fully exert their adsorption capacity, resulting in waste. Reducing the thickness of the LDH layer to at least one layer or a single layer can significantly change the physical and chemical properties of the material, increase the exposed surface, and optimize the metal adsorption capacity. However, the commonly used methods currently have the problem of being difficult to mass produce and difficult to scale up. The few-layer hydrotalcite prepared by dissociation is extremely easy to repolymerize into blocks, and there are few reports of few-layer LDHs that can be effectively used for heavy metal adsorption in soil and water.

[0036] Based on this, the present invention provides a method for synthesizing ultra-thin hydrotalcite sheet materials assisted by low dielectric constant solvents and ultrasound, and its application in adsorbing and removing Cr(VI) in soil and contaminated water. Under the same Cr(VI) removal performance, the amount of LDH can be significantly reduced, the efficiency can be improved, and the cost can be reduced.

[0037] Embodiment 1:

[0038] Nickel aluminum layered double hydroxide (NiAl-LDH) was synthesized by coprecipitation method. 5.3g NiSO4·6H2O (equivalent to 0.02mol Ni(II)) and 3.3g Al2(SO4)3·18H2O (equivalent to 0.01mol Al(III)) were used and dissolved in a conical flask in 50mL deionized water. Then, 2M NaOH solution was slowly dripped into the flask, and nitrogen was injected while stirring continuously (800rpm) to maintain an oxygen-deficient environment. The pH value of the suspension was monitored in real time. When it reached 9.0±0.5, the flask was placed in a 75℃ water bath and heated for 12 hours. After the heating process was completed, the suspension was cooled, washed three times with deionized water, and centrifuged to collect the precipitate. Finally, the precipitate was freeze-dried for 12 hours to obtain NiAl-LDH powder.

[0039] Embodiment 2:

[0040] To synthesize single-layer nickel aluminum layered double hydroxide (NiAl-LDH), 5.3 g NiSO4·6H2O (equivalent to 0.02 mol Ni(II)) and 3.3 g Al2(SO4)3·18H2O (equivalent to 0.01 mol Al(III)) were used and dissolved in a conical flask in 50 mL of deionized water. Then, ultrasound-assisted dissolution was performed in the presence of 30.0% by volume of formamide, and 2 M NaOH solution was slowly dripped into the flask. The pH value of the suspension was monitored in real time. When it reached 9.0±0.5, nitrogen was injected while continuously stirring (800 rpm) to maintain an oxygen-deficient environment. The fully dispersed solution formed a colloidal material, which was concentrated by centrifugation, and the washing and centrifugation with ethanol were repeated about three times to obtain a gel-like sample FU-NiAl-LDH.

[0041] Test Example 1:

[0042] First, a 40 mg / L hexavalent chromium (Cr(VI)) aqueous solution was prepared, which was Cr2O7 2- The anionic form was present by dissolving an appropriate amount of K2Cr2O7 in deionized water. Next, 0.15 g of NiAl-LDH was added to 20 mL of Cr(VI) solution (40 mg / L), and nitrogen (N2) was continuously introduced into the solution during the entire Cr(VI) removal process. The experiment was carried out three times in a thermostatic oscillator at an oscillation rate of 200 rpm and a temperature of 30 °C. Under continuous oscillation, samples were taken from the suspension at selected reaction times of 0, 5, 10, 20, 40 and 60 min and immediately filtered through a membrane filter with a pore size of 0.45 μm to facilitate the analysis of the remaining Cr(VI) content in the filtrate.

[0043] To investigate the effect of NiAl-LDH on the removal of hexavalent chromium (Cr(VI)) from soil, the following experimental steps were performed. The local soil was collected and air-dried under natural conditions, and then fresh fine soil was screened out through a 100-mesh sieve and stored in a vacuum desiccator for experimental use. The method for preparing hexavalent chromium (Cr(VI)) contaminated soil was as follows: a certain amount of 1000 mg / L Cr(VI) solution was mixed with soil in a mixing ratio of soil: liquid = 1:1. After that, the mixture was dried overnight. 0.05 g NiAl-LDH and 1.0 g soil containing Cr(VI) were added to a reaction tube in 5 mL ultrapure water to ensure the homogeneity of the mixture. The mixture was subjected to solid-liquid separation at selected reaction times of 0, 10, 20, 40, 60, and 90 min to facilitate the analysis of the concentration changes in the soil after Cr(VI) adsorption.

[0044] Test Example 2:

[0045] First, a 40 mg / L hexavalent chromium (Cr(VI)) aqueous solution was prepared, which was Cr2O7 2- The anionic form was present by dissolving an appropriate amount of K2Cr2O7 in deionized water. Next, 0.15 g of FU-NiAl-LDH was added to 20 mL of Cr(VI) solution (40 mg / L), and nitrogen (N2) was continuously introduced into the solution during the entire Cr(VI) removal process. The experiment was carried out three times in a thermostatic oscillator at an oscillation rate of 200 rpm and a temperature of 30 °C. Under continuous oscillation, samples were taken from the suspension at selected reaction times of 0, 5, 10, 20, 40 and 60 min and immediately filtered through a membrane filter with a pore size of 0.45 μm to facilitate the analysis of the remaining Cr(VI) content in the filtrate.

[0046] To investigate the effect of FU-NiAl-LDH on the removal of hexavalent chromium (Cr(VI)) from soil, the following experimental steps were performed. The local soil was collected and air-dried under natural conditions, and then fresh fine soil was screened out through a 100-mesh sieve and stored in a vacuum desiccator for experimental use. The method for preparing hexavalent chromium (Cr(VI)) contaminated soil was as follows: a certain amount of 1000 mg / L Cr(VI) solution was mixed with soil in a mixing ratio of soil: liquid = 1:1. After that, the mixture was dried overnight. 0.05 g FU-NiAl-LDH and 1.0 g Cr(VI)-containing soil were added to a reaction tube in 5 mL ultrapure water to ensure the homogeneity of the mixture. The mixture was subjected to solid-liquid separation at selected reaction times of 0, 10, 20, 40, 60, and 90 min to facilitate the analysis of the concentration changes in the soil after Cr(VI) adsorption.

[0047] It can be known from the above experimental results that: in the present invention, by introducing formamide and microwaves in the synthesis process of nickel aluminum hydrotalcite, the accumulation of lamellae is significantly suppressed, the thickness of the lamellae is reduced, and its adsorption capacity for hexavalent chromium is enhanced. Nickel, as the main active component, has unique chemical properties, such as excellent redox ability and stable chemical structure, which makes NiAl-LDH show excellent effects in removing heavy metal ions. The NiAl-LDH material prepared by this method can be widely used in the fields of water treatment and soil remediation, especially in the removal of toxic hexavalent chromium. This material is not only suitable for industrial wastewater treatment, but also suitable for the remediation of contaminated soil, providing an effective and reliable solution for environmental protection.

[0048] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0049] The above description enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An application of an ultra-thin nickel-aluminum hydrotalcite sheet material, characterized in that: The application is to remove Cr(VI) from wastewater and soil; The preparation method of the ultra-thin nickel-aluminum hydrotalcite sheet material comprises the following steps: S1: dissolving appropriate amounts of nickel sulfate and aluminum sulfate in deionized water to prepare a metal salt solution; S2: The solution is placed in a conical flask to ensure sufficient reaction; S3: introducing 2% to 30% formamide by volume and promoting the dissolution and reaction of the compound under the assistance of ultrasound; S4: Subsequently, while continuously stirring, slowly adding an appropriate amount of alkaline solution to adjust the pH value and promote the formation of NiAl-LDH; S5: As the reaction proceeds, a colloidal material is formed, and then the colloidal material is concentrated by centrifugation; S6: Then, ethanol is used for multiple washing and centrifugation to remove impurities and unreacted residues, thereby obtaining a high-purity gel-like ultrathin nickel-aluminum hydrotalcite sample FU-NiAl-LDH; In step S1, the molar ratio of nickel to aluminum is 2-3:0.5-1; In step S3, the alkaline solution is a sodium hydroxide solution; In the step S4, the pH value of the solution is controlled to be 9-11 during the process of adjusting the pH value and promoting the formation of NiAl-LDH; In step S3, the ultrasonic power is 1 W / cm 2 .

2. The use of an ultra-thin nickel-aluminum hydrotalcite sheet material as claimed in claim 1, characterized in that: The application comprises the following steps: S1: First, a Cr(VI) aqueous solution of a certain concentration was prepared by dissolving an appropriate amount of K2Cr2O7 in deionized water; S2: Then, LDHs were added to the Cr(VI) aqueous solution and adsorption experiments were performed. During the entire removal process, nitrogen was continuously introduced into the solution to maintain an inert atmosphere. S3: It is carried out in a thermostatic oscillator, by setting a specific oscillation rate and temperature, sampling at multiple predetermined time points and filtering through a microporous filter to analyze the remaining Cr(VI) content in the filtrate.

3. The use of an ultra-thin nickel-aluminum hydrotalcite sheet material as claimed in claim 2, characterized in that: The concentration of the Cr(VI) aqueous solution is 10-100 mg / L.

4. The use of an ultra-thin nickel-aluminum hydrotalcite sheet material as claimed in claim 2, characterized in that: The concentration of the LDHs in the Cr(VI)-containing aqueous solution and soil is 5-15 g / L.

5. The use of an ultra-thin nickel-aluminum hydrotalcite sheet material as claimed in claim 2, characterized in that: The speed of the constant temperature oscillator is 100-300 rpm, and the temperature is 25-40°C.

6. The use of an ultra-thin nickel-aluminum hydrotalcite sheet material as claimed in claim 2, characterized in that: The sampling time for removing Cr(VI) from the solution is 0 to 60 min; The sampling time for removing Cr(VI) from the soil is 0 to 90 minutes.

Citation Information

Patent Citations

  • Preparation method of calcined magnesium-aluminum hydrotalcite film

    CN109012573A